Understanding the Negative Impacts of Rigid Instituional Framework on Community Development Projects: A Case From Bangladesh - UPOMA BAIDYA, EMERALD (Alanya Hamdullah Emin Pa?a ?niversitesi, 2019)
The goal of this article is to analyse the participatory process of development projects. Drawing upon my professional experience in a project called Pre-Poor Slum Intergration Project (PPSIP) which was based in Comilla, Bangladesh - I argue that development projects dominated by rigid power structures inside and in-between institutions inhibits community participation that reflects the actual need of the beneficiary group; and as happened in this case, produce results that do not serve the people in real need but rather only serve the purpose of the institutions that manage the project, more so the institutions having higher degrees of power. In this article I try to combine insights gained from our field experience and literature study on post-politics and power in planning in order to sketch out the stakeholder institutions' interest, capacity and enrolment in order to understand how socio-relational dynamics as opposed to technical procedures shaped the project. In this project participation from the community was ritualistic- serving only a face-value, the operational team on the field were devoid of power to take important decisions or challenge the institutional framework that they were part of, and at the same time institutions with higher degrees of decision making power were not sufficiently involved with the realities of the field. I conclude that in order to make participatory process really work, involved institutions should not limit their efforts in repetitive consensus building exercises based on pre-conceived ideas and traditional methods of community development.